Measures of International Transport Cost for OECD Countries - Golub, Stephen S.. (OECD Economics Department Working Papers, 2008)
This paper presents new estimates of country-specific international transport costs for 21 OECD countries over the period 1973-2005. The methodology is based on direct measures of air, maritime, and road transport costs rather than on cif/fob ratios or other balance of payments data employed in previous studies. Transport costs are calculated as costs per kilogramme for each mode of transport at a bilateral level and then aggregated. Australia and New Zealand are found to have the highest transport costs among the OECD countries considered, followed by Japan. The time trends are sensitive to the choice of deflator, but the results do not show an overall downward trend in transport costs for OECD countries, contrary to conventional wisdom, but consistent with Hummels' (2007) recent study of global transport costs